The Impact of Speed Endurance Training by using High-Intensity Interval Method on Developing Ball Running Skill Among football Players - under 19 years - - Belafrites , Yacine; Ghannam , Noureddine (sports creativity, 2025)
The aim of this study was to identify The impact of Training by Using High-Intensity interval method in developing the speed _ Endurance and the performance level of Ball running skill among the football players- under 19 years-. The sample of the study included (32) players under 19 years, they were chosen deliberately. The experimental group received the proposed training program, while the control group was trained traditionally, the experimental approach was used to suit the nature of the study. The two groups received two test (Test of speed endurance , and Ball running test) before applying the proposed training program for a period of 10 weeks, and post test measurement was administered at the end of the proposed training program. After conducting the y statistical treatment, the results of the study showed that the proposed training program has a positive impact on the development of speed endurance and the skill of running with the ball as well. There is a strong statical correlation between the development of speed endurance and improving the skill of running with the ball for football players -under 19 years-, where the members of the experimental group exceeded The members of the control group which means that the tests results on the experimental group were more effective in the post tests